Pengaruh Live Streaming Selling dan Diskon Pada Aplikasi Tiktok Shop Terhadap Perilaku Impulse Buying: (Studi Kasus Pada Mahasiswa Universitas Sumatera Utara Kota Medan) - Khairani, Anisya; Jumasa Surbakti, Felix; Ramadhan Siagian, Muhammad Fathur; Br Bangun, Virgin Threisia; Sari Saragih, Mernita (PT. Alahyan Publisher Sukabumi, 2024)
This study aims to determine the effect of Live Streaming Selling and Discounts on the Tiktok Shop application on Impulse Behavior Buying Behavior in University of North Sumatra Students. The dependent variable in This study is Live Streaming Selling and Discounts while the dependent variable is Impulse Buying. the dependent variable is Impulse Buying. Population and sample research is a student of the University of North Sumatra with a total respondents as many as 100 students. The data obtained was analyzed using PLS analysis technique (Partial Least Square through Smart PLS software and SPSS application). SPSS application). Partial data will be processed with PLS analysis techniques, while simultaneously processed with the SPSS application. while simultaneously processed with the SPSS application. Based on the results of the study, it can be concluded that R-Square found that live streaming, selling, and discounts together only explain 11.4% of the variation in impulse buying behavior.